Effect of microbial inoculants on the chemical composition and aerobic stability of Tanzania guinea grass silages - Bumbieris Junior, V. H.; Horst, E. H.; Guimaraes, V. A. P.; Massaro Junior, F. L.; Moraes, G. J.; Meza, D. A. R. [UNESP]; Galbeiro, S. (South African Journal Of Animal Sciences, 2021)
The present study evaluated the effects of microbial inoculants on chemical changes and aerobic stability efficiency in Tanzania guinea grass silage. The treatments consisted of C: silage without inoculant; I: silage inoculated with Lactobacillus plantarum (CCT 0580) 8.0 x 10(9) CFU g(-1), Bacillus subtilis (CCT 0089) 2.0 x 10(9) CFU g(-1), and Pediococcus acidilactici (CCT 2553) 1.0 x 10(10) CFU g(-1), and L: silage inoculated with Lactobacillus plantarum (CCT 0580) 2.6 x 10(10) CFU g(-1) and Pediococcus pentosaceus (CCT 7659) 2.6 x 10(10) CFU g(-1). The experimental design was completely randomized, with five replications. There were no treatment effects on the nutritional composition of the silages, but both inoculants were effective in reducing the pH of the silage to 4.80 and 4.83 for I and L, respectively, compared with 5.04 for C. Silage with L had a lower ammonia nitrogen (N-NH3) content than the other silages (9.83%). Despite the lower pH values, the use of inoculants did not reduce fungal and yeast counts or improve the aerobic stability of Tanzania guinea grass silages.
Keywords: aerobic deterioration; ammonia nitrogen; lactic bacteria; Panicum maximum; spoilage microorganisms